2021
DOI: 10.3390/molecules26165017
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activity and Phenolic Content of Extracts Derived from Cypriot Carob (Ceratonia siliqua L.) Pods Using Different Solvents

Abstract: Extracts derived from the Ceratonia siliqua L. (carob) tree have been widely studied for their ability to prevent many diseases mainly due to the presence of polyphenolic compounds. In this study, we explored, for the first time, the anti-cancer properties of Cypriot carobs. We produced extracts from ripe and unripe whole carobs, pulp and seeds using solvents with different polarities. We measured the ability of the extracts to inhibit proliferation and induce apoptosis in cancer and normal immortalized breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 70 publications
(80 reference statements)
3
25
0
1
Order By: Relevance
“…To our knowledge, although there is no information linking carob and cell death in animals, research on carob’s effect on the apoptotic pathway has been extensively studied in cancer cells and cancer cell lines. These studies have shown that carob induces apoptosis in cancer cells and inhibits their proliferation (e.g., [ 78 , 79 , 80 ]). The underlying mechanism is attributed to the inhibition of the activation of the AKT pathway, which in turn leads to the activation of the apoptotic pathway [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, although there is no information linking carob and cell death in animals, research on carob’s effect on the apoptotic pathway has been extensively studied in cancer cells and cancer cell lines. These studies have shown that carob induces apoptosis in cancer cells and inhibits their proliferation (e.g., [ 78 , 79 , 80 ]). The underlying mechanism is attributed to the inhibition of the activation of the AKT pathway, which in turn leads to the activation of the apoptotic pathway [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that carob induces apoptosis in cancer cells and inhibits their proliferation (e.g., [ 78 , 79 , 80 ]). The underlying mechanism is attributed to the inhibition of the activation of the AKT pathway, which in turn leads to the activation of the apoptotic pathway [ 79 ]. In the present study, a concentration-dependent beneficial effect on T. molitor larvae was shown.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are phytochemicals that contribute to the improvement of human health and prevention of numerous diseases, including cardiovascular diseases, oxidative stress and cancer, and exhibit neuroprotective properties due to their antioxidant and anti-inflammatory activities [ 21 ]. Carob polyphenolic extracts have been demonstrated to display anti-proliferative and apoptotic activity against cancer cells, in addition to anti-diabetic, anti-diarrheal and anti-hyperlipidemic effects [ 22 , 23 , 24 , 25 , 26 , 27 ]. The major polyphenols present in carob include free, bound and conjugated forms of phenolic acids, flavonols, flavan-3-oles, hydrolysable tannins and proanthocyanidins with significant biological activities [ 2 , 17 , 23 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carob polyphenolic extracts have been demonstrated to display anti-proliferative and apoptotic activity against cancer cells, in addition to anti-diabetic, anti-diarrheal and anti-hyperlipidemic effects [ 22 , 23 , 24 , 25 , 26 , 27 ]. The major polyphenols present in carob include free, bound and conjugated forms of phenolic acids, flavonols, flavan-3-oles, hydrolysable tannins and proanthocyanidins with significant biological activities [ 2 , 17 , 23 , 24 , 26 ]. The polyphenolic content of carob powder can be influenced through competing pathways upon roasting, as the thermal degradation of phenolic compounds can lead to decreased antioxidant activity, while higher extractability of phenolic compounds from the complex food matrix upon heating has been suggested to increase availability and, consequently, to induce the opposite effect on antioxidant activity [ 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…относительно суровые условия обитания и характеризуется устойчивостью к вредителям и болезням, приспособляемостью к засухе, бедным и каменистым почвам), ее выращивание приносит экономическую выгоду (на национальном и региональном уровнях -в качестве стабильного источника дохода местного населения за счет получения продукции из плодов и семян) [3][4][5]. Семена бобов цератонии используются как промышленное сырье для производства ценного полисахарида, являющегося пищевой добавкой -камедь рожкового дерева (Е-410), представляющей собой порошок измельченного эндосперма семени [6,7].…”
unclassified